Cover Image, Volume 70, Issue 6. Issue 6 (13th May 2021) - Strutton, Jared W; Knott, Matthew; Bencomo, Jose A; Iacono, Scott T; Mates, Joseph E; Alston, Jeffrey R; McCollum, Jena M
Abstract : The cover image is based on the Research Article Manipulating polymer decomposition to alter burn performance in aluminium/poly(vinylidene fluoride) filaments by Jared W. Strutton et al., https://doi.org/10.1002/pi.6129 . Abstract : The cover image is based on the Research Article Manipulating polymer decomposition to alter burn performance in aluminium/poly(vinylidene fluoride) filaments by Jared W. Strutton et al., https://doi.org/10.1002/pi.6129 .